Research on Bibliometric Analysis of Lawson Classroom Test of Scientific Reasoning in the Past Ten Years - Noly Shofiyah; Budi Jatmiko; Nadi Suprapto (Indonesia Approach Education, 2023)
The Lawson Classroom Test of Scientific Reasoning (LCTSR) is a popular instrument that measures the development of students’ scientific reasoning skills. Through large-scale applications, several issues have been observed in terms of validity, scoring, and the way of interpretation. This study aims to identify the contribution and describe the research profile of applying LCTSR in education during the last ten years. The method used in this research is a bibliometric analysis based on Scopus data with the help of Biblioshiny and VOSviewer. The study obtained 43 documents related to LCTSR. The results showed that the use of LCTSR every year has increased and decreased in the last ten years. Journals and proceedings in the field of physics dominate the publication sources for LCTSR research. Furthermore, Bao, Koenig, and Xiao were the three most prolific authors and also had research collaborations. The dominant country for publication is the United States. The area most often associated with LCTSR research is social science, whose purpose is to measure the development of student’s cognitive abilities. The scope of this research analysis is limited to certain databases or languages, so this study recommends finding renewed discussions about the use of LCTSR in education over a longer period.